The COVID-19 Pandemic Affects Male Patients With Chronic Spontaneous Urticaria More Than Female Patients - Kulu, Huzeyfe; Atasoy, Mustafa; Özyurt, Kemal; Maurer, Marcus; Avcı, Atıl; Akkuş, Muhammet Reşat; Ertaş, Ragıp (Frontiers in Immunology, 2021)
Introduction: The COVID-19 pandemic dramatically disrupts health care for patients with chronic diseases including chronic spontaneous urticaria (CSU). As of now, it is unknown if the effects of the pandemic in CSU are different than in other chronic diseases. We also do not know, if different groups of CSU patients, for example female and male patients, are affected differently. Aim: To understand how CSU patients and subgroups are affected by the COVID-19 pandemic in their disease activity and control and treatment, using psoriasis as control. Patients and methods: We analyzed 399 patients (450 visits) with CSU or psoriasis assessed during August 2019, i.e. before the pandemic, or August 2020, i.e. during the pandemic, for changes in disease activity, disease control, and the treatment they used, and how these changes are linked to age, gender, and disease duration. Results: Male but not female patients with CSU had markedly increased disease activity during the pandemic. CSU patients’ age or disease duration were not linked to changes. Male and female patients with psoriasis showed similar increases in disease activity and decreases in disease control. The rate of omalizumab treatment, during the pandemic, was unchanged in male patients and increased in female patients with CSU. The efficacy of omalizumab treatment, during the pandemic, was reduced in male patients but not female patients with CSU. Conclusion: Male but not female CSU patients, during the COVID-19 pandemic, show loss of disease control linked to loss of omalizumab efficacy. The reasons for this need to be investigated.